Research on related factors of hyperuricemia in high altitude area migrant population - Meng, Dong-Dong; Kang, Yin-Dong; Chang, De-Hui (Frontiers in Endocrinology, 2025)
BackgroundHyperuricemia, a prevalent metabolic disorder, is witnessing a global annual increase in incidence. The gout it triggers and its link to other chronic diseases pose a severe threat to human health. The unique natural environment of high-altitude regions, characterized by low oxygen partial pressure and cold climate, may exert a distinctive influence on human metabolism, thereby impacting the onset and progression of hyperuricemia.MethodsThis study recruited 284 plateau migrants undergoing physical examinations at Ritu County Hospital from June to December 2024. Among them, 224 had hyperuricemia and 60 had normal uric acid levels. It collected various indicators of all subjects, including general demographic information, blood routine parameters, and biochemical markers. For univariate analysis, the t-test was used for continuous variables and the chi-square test for categorical variables to screen potential factors related to hyperuricemia. Then, a multicollinearity analysis was done on the univariate factors. After excluding variables with a VIF greater than 5, the remaining ones were put into the multivariate logistic regression model to identify the independently related factors of hyperuricemia.ResultThe incidence of hyperuricemia in the study population was 78.87%. Variables such as gender, age, red blood cell count and creatinine were found to be independently associated with hyperuricemia.ConclusionThis study revealed an elevated incidence of hyperuricemia in high-altitude area migrants and identified its independent related factors, offering a crucial foundation for the prevention and treatment of hyperuricemia in these regions.